Origin of cultivated rice - Oka, H. I. (Japan Scientific Societies, 1988)
Ecology and population biology of the common wild rice, genetic variations and envolutionary dynamics, the homeland of oryza sativa, Indica-japonica differentiation of rice cultivars, funtions and genetic bases of reproductive, variations in adaptability to environment, and germplasm conservation.